The Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) Scale: A New Instrument for Assessing the Anxiety Response of General Population to the Viral Epidemic During the COVID-19 Pandemic - Chung, Seockhoon; Ahn, Myung Hee; Lee, Sangha; Kang, Solbi; Suh, Sooyeon; Shin, Yong-Wook (Frontiers in Psychology, 2021)
The general population has reported experiencing anxiety due to the COVID-19 pandemic. This study explored the validity and utility of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale for measuring the anxiety response of the general population to the viral epidemic. About 1,009 respondents participated in an online survey. Of these, 501 (49.7%) participants were rated as having at least a mild degree of anxiety response to the viral epidemic (SAVE-6 score ≥ 15), while 90 (8.9%) and 69 (6.8%) participants were rated as having moderate degree of depression and anxiety, respectively. The SAVE-6 scale showed a good internal consistency (Cronbach’s alpha = 0.815). Parallel analysis suggested a one-factor structure for the measure. The SAVE-6 scale was found to be a reliable, valid, and useful brief measure that can be applied to the general population.